Role of multidetector computed tomography in evaluation of abdominal trauma in Sothern Rajasthan, India - ., Puran; Kardam, Narendra Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Abdominal injury constitutes a significant portion of all blunt and penetrating body injuries. Computed tomography is an important and fast technique which gives rapid information on the type of abdominal injury and helps in management of the patient accordingly. The aim of the present study was to evaluate the usefulness of Multidetector Computed Tomography (MDCT) in detection of intra-abdominal injury in patients with blunt abdominal trauma and to provide information that could accurately determine choice of management (non- operative versus operative). And to correlate the computed tomography (CT) findings with either clinical observation, follow up CT scan (if required) or surgical findings (wherever applicable). Methods: A total of 50 patients with abdominal trauma who underwent computed tomography (CT) examination were included. CT findings were compared with surgical findings in operated cases, and in the rest CT findings were compared by clinical outcome. Results: Among the 50 cases studied, all 50 had positive CT findings of abdominal trauma, out of which 24 patients underwent surgery and the remaining were managed conservatively. The age group of the patients was ranging from 8 to 66 years with male predominance. In this study the commonest organs affected were liver and spleen accounting for 48% and 44% respectively. Conclusions: Computed tomography is an important and highly sensitive imaging modality for diagnosis of organ injuries in patients with abdominal trauma and accordingly deciding the management of patient.